Chemokines and Their Receptors: Roles in Specific Clinical Conditions and Measurement in the Clinical Laboratory - Locati, Massimo (Pathology Patterns Reviews, 2005)
Considerable progress has been achieved in our knowledge of the function of the chemokine system and in understanding its role in the pathophysiology of human diseases. This complex system, presently including approximately 50 cytokines and 20 receptors, coordinates leukocyte recruitment in a variety of human diseases, ranging from infectious and inflammatory diseases to cancer. A large body of literature has been published describing various assays for the measurement of chemokines in biologic fluids and tissues. We review information available on the role of chemokines in selected human diseases and provide examples of clinical situations in which chemokine determination might be of practical value, and we describe the currently available assays for their measurement.